I worship, so I download? Idol worship, music purchase and piracy by young consumers in Taiwan - Yu-An Huang; Lin, Chad; Hung-Jen Su; Mei-Lien Tung (Emerald, 2015)
Design/methodology/approach – A stratified, two-stage, cluster sampling procedure was applied to a list of high schools obtained from the Ministry of Education in Taiwan. A return rate of 80 per cent yielded 723 usable questionnaires, the data from which were analysed by the LISREL structural equation modelling software. Findings – The results suggest that both social worship and personal worship have a significant and positive impact on the intention to purchase music. However, personal worship has a negative impact on the intention to pirate music while social worship appears to strengthen it. Research limitations/implications – The findings suggest that idol worship is more complex than previously understood. The constructs chosen in this research should be seen only as a snapshot but other variables such as vanity trait, autonomy, romanticism or involvement are not taken into account. Future studies would benefit from inclusion of these variables and a wider geographical scope. Practical implications – The findings contain many implications to help marketing executives and planners better revise their existing marketing and communication strategies to increase their revenue. Originality/value – Existing research has tended to examine the impact of idol worship as a whole on the reduction of music piracy, but overlook the two-dimensional aspects of idol worship, hence ignoring the fact that many music firms have not properly utilised idol worship to deal with the challenges associated with music piracy. The findings broaden existing understanding about the causes of two different dimensions of idol worship and their different impacts on the intention to music piracy.